Expanding the eco-evolutionary context of herbicide resistance research - Neve, Paul (2014)
The potential for human-driven evolution in economically and environmentally important organisms in medicine, agriculture and conservation management is now widely recognised. The evolution of herbicide resistance in weeds is a classic example of rapid adaptation in the face of human-mediated selection. Management strategies that aim to slow or prevent the evolution of herbicide resistance must be informed by an understanding of the ecological and evolutionary factors that drive selection in weed populations. Here, we argue for a greater focus on the ultimate causes of selection for resistance in herbicide resistance studies. The emerging fields of eco-evolutionary dynamics and applied evolutionary biology offer ameans to achieve this goal and to consider herbicide resistance in a broader and sometimes novel context. Four relevant research questions are presented, which examine (i) the impact of herbicide dose on selection for resistance, (ii) plant fitness in herbicide resistance studies, (iii) the efficacy of herbicide rotations and mixtures and (iv) the impacts of gene flow on resistance evolution and spread. In all cases, fundamental ecology and evolution have the potential to offer new insights into herbicide resistance evolution and management.